A STUDY ON THE CURRENT "NATIONAL CYBER SECURITY STRUCTURE" IN MONGOLIA - Sukhbaatar Shirbazar; Baasandamba Dashtseden (International Journal of Innovative Technologies in Social Science, 2024)
According to one of the six components of Mongolia’s national security concept, the country’s national cyber security structure was established within the framework of the "On National Security," "On Cyber Security," and "On Armed Forces" laws. Despite these efforts, Mongolia’s information and cyber security remain inadequate. Consequently, there is an urgent need to enhance the unified national system for protecting Mongolia’s cyberspace. This involves clearly defining the roles and functions of the state, society, and citizens, as well as updating policies and legal regulations to ensure coordinated efforts among the organizations involved in the system.